A Description in the poetry of the obscure and the venerable for the fifth and sixth centuries AH - Hammoud, Salah; Al-Helou, Wassan (Al-Adab Journal, 2025)
Description is the basis on which the poet builds his poem, to the point that it has been said that poetry is based solely on description. The ancients, especially in the eras that preceded the Abbasids, were swayed by including it mixed with other purposes, and they did not intend it to describe the single poetic purpose that flourished and became a characteristic of the Abbasid era, especially the fifth and sixth centuries AH. The poets of this stage surpassed all those who preceded them and developed significantly on two fronts: the first: that he became independent and intentional, and the second: introducing new meanings to the things described, especially among them the decrease in the frequency of describing the desolate desert and the pre-Islamic environment to describing meadows, orchards, castles, fortresses, and everything that their searching eyes fell upon. Examining the particles of what surrounds them, including describing the cold weather, snow, schools, describing types of food, describing pens and notebooks, and other things that poets excelled at, and all of that would not have happened had it not been for the development of the mental life of the Arab individual and society towards civilization. Then the environment in which he inhabits has a role in revealing this new description, especially They left the desert for the cities.